The Role of the Bulungan Police Four-Wheel Patrol in Reducing the Crime of Theft with Aggravated Circumstancesin Bulungan - Fardan Adi Nugroho (Police Studies Review, 2021)
The Indonesian National Police (Polri) are state servants in maintaining security and public order. The high incidence of weighted theft in Bulungan Regency is the background of this research. The purpose of this study is to know and analyze the description of Curat's actions in Bulungan, to find out the role of the SatSabhara patrol unit of the Bulungan Police in carrying out patrol activities and the factors factors affecting patrol activities by SatSabhara Polres Bulungan. This research is a research using qualitative methods. Qualitative research includes primary, secondary and tertiary data in carrying out research conducted at the Bulungan Police. The technology, which in its implementation uses the four-wheeled Isuzu MUX brand, b. This market is aimed at public places so that the public is safe, (2) The inhibiting factor, namely human beings, is related to the number of SatSabhara personnel, Bulungan Police, as many as 396 people, according to Chief of Police Perkap No. 23/2010 describes the ideal of Bulungan Police personnel needing 1062 people, b. The money received is still limited, only the need for patrols without funding for firearms while on duty, c.The material in question still lacks facilities such as HT and four- wheeled vehicles so that the hope can be increased facilities to support the SatSabhara patrols, d.The methods still need to be improved, both the responsibility between personnel and the two-way patrol plan.